Late Onset Meningitis in Post Traumatic Temporal Meningoencephalocele - Sadr, Zahra; Noorbakhsh, Samileh; Zafaranloo, Nazanin; Moshfegh, Fereshteh; Nasoori, Yaser (Journal of Diseases, 2022)
Temporal lobe meningoencephalocele is an uncommon anomaly in the face. As brain tissue herniate through the dural imperfection, cerebrospinal fluid (CSF) or a mass will appear in the mastoid, middle ear or the both. Here we present a 10 years old boy with right lobe temporal meningoencephalocele which results in CSF leakage and manifested with bacterial meningitis. He had a history of head trauma and bone fracture 3 years ago. In surgery the defect repaired and the patient showed improvement.
Keywords: bacterial meningitis; meningoencephalocele; temporal lobe